The domestic participation in birth assistance in the mid-twentieth century - Elena Andina Díaz; José Siles González
Abstract Objective: to describe how the progressive creation of the Social Security (providing widespread health care) affected the birth assistance in Spain from the 1940s to the 1970s in a rural area. Method: historical ethnography. Twenty-seven people who lived at that time were selected and interviewed guided by a semistructured script. Based on their testimonies, a chart was built with the functional elements involved in birth assistance in this region. Results: three agents performed such care: traditional midwives, women of the family/neighbors and health workers. Conclusion: although birth assistance had been transferred to the hands of the health workers from the forties in this region, women in labor continued to count on the domestic resources until the early seventies, when births were compulsorily transferred to hospitals. This research brings to light the names and recognizes the work performed by these female characters of the popular sphere, who helped women in labor of that community to give birth, for at least three decades.